FRI0413 Comparison of C-Reactive Protein, High Sensitivity C-Reactive Protein and Erythrocyte Sedimentation Rate with Disease Activity in Lupus. (10th June 2014) - Moder, K.G.; Crowson, C.S.; Snyder, M.R.; Saenger, A.K.; Matteson, E.L.
Abstract : Background: It is uncertain which acute phase reactant, C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR) correlates best with disease activity in patients with systemic lupus erythematosus (SLE). Objectives: The objective of this study was to determine which acute phase reactant correlated best with disease activity in patients with SLE. Methods: All patients enrolled met American College of Rheumatology classification for SLE and were evaluated by rheumatologists. All patients had simultaneous measurement of CRP, high sensitivity CRP (hsCRP), and ESR. CRP and hsCRP were analyzed on the Roche Modular System, and ESR was measured by the Westergren method. Disease activity assessment was done by SLEDAI score. Results: Of 80 patients enrolled, 65 were female (81%) and the mean age of the patients was 46.6 years (range 23 to 79). 56 patients (70%) had active disease defined as SLEDAI score >0. The mean CRP was 5.4 mg/L (range <3 to 37.9, median <3) with 10 elevated values (>8 mg/L). hsCRP was measured in the first 49 subjects enrolled in the study. The mean hsCRP was 4.2 mg/L (range 0.17 to 30.1, median 2.42) with 6 elevated values (4 corresponding to abnormal CRP values and 2 additional). The mean ESR was 17.6 mm/1 hr (range 1-95, median 13) with 16 elevated values (>22 for males, >29 for females). Both ESR and CRP were significantly correlated with SLEDAI scores (r=0.22, p=0.046, and r=0.37, p<0.001, respectively using the Spearman method). hsCRP was highly correlated with CRP (r=0.90, p<0.001) and SLEDAI (r=0.36, p=0.01) but not with ESR (r=0.10, p=0.47). ESR and CRP also did not correlate with each other (r=0.17, p=0.14). Elevated ESR was significantly associated with higher SLEDAI scores (p=0.002 by rank sum test) as was elevated CRP (p=0.03). Patients that had an elevated ESR, elevated CRP or both had significantly higher SLEDAI scores than those with normal ESR/CRP (p=0.002). By use of linear regression models, ESR and CRP were found to be independently associated with SLEDAI scores (ESR p=0.01; CRP p<0.001). hsCRP was not independently associated with SLEDAI after adjustment for ESR and CRP (p=0.58). ESR was elevated in 14/56 (25%) patients with active lupus while CRP was elevated in 8/56 (14%) patients. ESR was more likely to be elevated in active disease than CRP (p=0.10). However, 18/56 (32%) patients that had active disease had either an elevated CRP, ESR or both. Only 4 (17%) of the 24 patients with inactive lupus had elevation in CRP or ESR. Conclusions: ESR was more likely to be elevated in active lupus than CRP. However, both correlated with disease activity and neither were elevated in all patients with active disease. Additional measurement of hsCRP was not helpful. In lupus patients who have a normal ESR and normal CRP, active disease is still common. References: Feldman M, Aziz B, Kang GN, Opondo MA, Belz RK, Sellers C: C-reactive protein and erythrocyte sedimentation rate discordance: frequency and causes in adults. Journal of Laboratory and Clinical Medicine 161(1):37-43, 2013 Jan. Amezcua-Guerra LM, Springall R, Arrieta-Alvarado AA, Rivera-Martinez E, Castillo-Martinez D, Bojalil R: C-reactive protein and complement components but not other acute phase reactants discriminate between clinical subsets and organ damage in systemic lupus erythematosus. Clinical Laboratory 57(7-8):607-13, 2011. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1073